Experimental study on water absorption and compressive strength of foamed concrete produced using eco-foaming agent - Chai, Teck Jung; Sulaiman, Haspina; Koh, Heng Boon (Faculty of Civil Engineering, 2025)
This paper presents the properties of foamed concrete using a plant based eco-foaming agent. Two series of foamed concrete, with target densities ranging from 1500 to 1800 kg/m3 were prepared using natural fine aggregates of varying particles sizes. Mix A (MA) incorporated aggregates passing a 2.36 mm sieve, while Mix B (MB) used aggregates passing a 1.18 mm sieve. The workability of fresh foamed concrete was assessed through spreadability tests. Hardened foamed concrete specimens were tested for compressive strength at 7, 14, and 28 days. Meanwhile, water absorption test was conducted at 28 days. The results revealed that MB exhibited higher compressive strength than MA at lower densities. Conversely, at higher densities, MA showed superior strength. MA also demonstrated slightly better spreadability, while MB had lower water absorption. These findings suggest that plant-based eco-foaming agents offer a sustainable and effective alternative for foamed concrete production.